Relative Efficacy of Dry-Off Antimicrobial Treatments in Dairy Cattle to Cure Existing Intramammary Infections: A Systematic Review and Network Meta-Analysis - McMullen, Carrie K.; Sargeant, Jan M.; Kelton, David F.; O'Connor, Annette M.; Reedman, Cassandra N.; Hu, Dapeng; Glanville, Julie; Wood, Hannah; Winder, Charlotte B. (Frontiers in Animal Science, 2021)
The objective of this systematic review and network meta-analysis was to estimate the relative efficacy of dry cow antimicrobial therapies to cure existing intramammary infections (IMI) in dairy cattle in Canada and the USA. Controlled trials examining all-cause cure of existing IMI present at dry-off were eligible. Five databases and four conference proceeding platforms were searched. Risk of bias at the level of the outcome was assessed using the Cochrane 2.0 risk of bias instrument, and the overall confidence in the findings from the network meta-analysis was assessed using the Confidence In Network Meta-Analyses (CINeMA) platform. Of 3743 articles screened for eligibility by two independent reviewers, 58 trials were included in the Bayesian network meta-analysis for all-cause cure of existing IMI from dry-off to calving. No antimicrobial treatment (non-active control) was associated with a decreased risk of a cure compared to all other currently labelled antimicrobials in Canada and the USA; however, lack of replication trials for some antimicrobial products created large credibility intervals and, therefore, we were unable to identify meaningful comparisons between products. Poor reporting of trial features, heterogeneity in outcome measurements, and high risk of bias in some domains further contributed to this inability to compare antimicrobials. Continued improvement in the reporting of animal trials is required in order to make recommendations for antimicrobial products on the basis of efficacy.